Quo Vadis Pendidikan Pesantren di Era Digital - Ali Rahmat; Anwar Rudi (Kariman: Jurnal Pendidikan Keislaman, 2023)
The results of this study indicate that the potential for the development of Islamic boarding schools in the digital era is quite wide open. We can observe this from the various strengths and potentials possessed by pesantren which are quite dominant. However, it turns out that the strengths and potential possessed by pesantren are not always a reference for the development of education in general. To implement education in the digital era, for example, there are still some perceptions that come from both internal and external pesantren who are worried about the fading of the core education of pesantren, namely the formation of human morality. Such a perception cannot be denied because implementing education in the digital era requires the readiness of adequate human resources in terms of knowledge, skills and mature personality so that they are able to utilize and respond to information technology in this digital era as a form of formulation of educational development in Islamic boarding schools.